A multimethod analysis of shared decision-making in hospice interdisciplinary team meetings including family caregivers. (March 2016) - Washington, Karla T; Parker Oliver, Debra; Gage, L Ashley; Albright, David L; Demiris, George
Background: Much of the existing research on shared decision-making in hospice and palliative care focuses on the provider–patient dyad; little is known about shared decision-making that is inclusive of family members of patients with advanced disease. Aim: We sought to describe shared decision-making as it occurred in hospice interdisciplinary team meetings that included family caregivers as participants using video-conferencing technology. Design: We conducted a multimethod study in which we used content and thematic analysis techniques to analyze video-recordings of hospice interdisciplinary team meetings ( n  = 100), individual interviews of family caregivers ( n  = 73) and hospice staff members ( n  = 78), and research field notes. Setting/participants: Participants in the original studies from which data for this analysis were drawn were hospice family caregivers and staff members employed by one of five different community-based hospice agencies located in the Midwestern United States. Results: Shared decision-making occurred infrequently in hospice interdisciplinary team meetings that included family caregivers. Barriers to shared decision-making included time constraints, communication skill deficits, unaddressed emotional needs, staff absences, and unclear role expectations. The hospice philosophy of care, current trends in healthcare delivery, the interdisciplinary nature of hospice teams, and the designation of a team leader/facilitator supported shared decision-making. Conclusion: The involvement of family caregivers in hospice interdisciplinary team meetings using video-conferencing technology creates a useful platform for shared decision-making; however, steps must be taken to transform family caregivers from meeting attendees to shared decision-makers.